Constraints on LISA Pathfinder's self-gravity: design requirements, estimates and testing procedures. (8th November 2016) - Armano, M; Audley, H; Auger, G; Baird, J; Binetruy, P; Born, M; Bortoluzzi, D; Brandt, N; Bursi, A; Caleno, M; Cavalleri, A; Cesarini, A; et al.
Abstract: LISA Pathfinder satellite was launched on 3 December 2015 toward the Sun–Earth first Lagrangian point (L1) where the LISA Technology Package (LTP), which is the main science payload, will be tested. LTP achieves measurements of differential acceleration of free-falling test masses (TMs) with sensitivity below 3 × 10 − 14 m s − 2 Hz − 1 / 2 within the 1–30 mHz frequency band in one-dimension. The spacecraft itself is responsible for the dominant differential gravitational field acting on the two TMs. Such a force interaction could contribute a significant amount of noise and thus threaten the achievement of the targeted free-fall level. We prevented this by balancing the gravitational forces to the sub nm s −2 level, guided by a protocol based on measurements of the position and the mass of all parts that constitute the satellite, via finite element calculation tool estimates. In this paper, we will introduce the gravitational balance requirements and design, and then discuss our predictions for the balance that will be achieved in flight.